2019
DOI: 10.1002/bit.27212
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of flow and interfaces on antibody aggregation

Abstract: During the manufacturing process, solutions of protein‐based drugs are exposed to hydrodynamic forces, which can potentially affect protein stability and aggregation. Despite being an area of extensive investigation, the effect of hydrodynamic flow on protein aggregation is still controversial. In this study, we designed an experimental setup that allowed us to investigate flow‐ and interface‐induced protein aggregation of two model immunoglobulins in the presence of well‐defined flow stresses and solid–liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 58 publications
4
26
1
Order By: Relevance
“…Using an array of proteins, including three IgG1 mAbs, we have also showed that extensional (and subsequent shear) flow induced by the EFD can trigger protein aggregation and that these effects were extremely protein‐ and flow‐field specific . More recently, EFDs of similar design to that employed in our study have been constructed and mAb aggregation observed under extensional and shear flows . These and other studies have shown that the presence and chemical composition of interfaces and presence of localized high protein concentrations within flow devices also contribute to the aggregation cascade.…”
Section: Discussionsupporting
confidence: 68%
“…Using an array of proteins, including three IgG1 mAbs, we have also showed that extensional (and subsequent shear) flow induced by the EFD can trigger protein aggregation and that these effects were extremely protein‐ and flow‐field specific . More recently, EFDs of similar design to that employed in our study have been constructed and mAb aggregation observed under extensional and shear flows . These and other studies have shown that the presence and chemical composition of interfaces and presence of localized high protein concentrations within flow devices also contribute to the aggregation cascade.…”
Section: Discussionsupporting
confidence: 68%
“…This result is supported by the previous observations on the fibril formation influenced by hydrodynamic flow 55 or interfacial factor 35,56 individually, as well as their synergistic effect. 57 The different degree of polymorphism in the different conditions is related to the environmental stress, which can thus be used to control the polymorphism of amyloid fibrils. 11,17,28,58 In this designed experiment, the environmental stress in the oscillating nonbubble and the static S-bubble condition were relatively weak, as shown on the environmental stress map (Figure 3j).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of many different non-amyloid proteins show that most resist aggregation even at very high shear rates [24]. However, in the presence of certain surfaces, solutions of these same proteins aggregate at much lower shear rates, some even without shear [25].…”
Section: Surface-and Flow-induced Aggregationmentioning
confidence: 99%
“…Shear experiments using Raman spectra to 468 explore protein backbone alterations have found that 469 similar order of magnitude shear rates reversibly alter quite different protein backbone conformations [43].These low shear rates contrast with some reported experiments where many orders of magnitude higher shear rates could not denature proteins. However, similar shear experiments in the presence of surfaces have demonstrated that, depending on the nature of the surface, certain surfaces can readily promote protein aggregation at very low shear rates[24, 44].Hydrophobic and polar surfaces were found to be quite effective in this regard.Biological membranes have distinct hydrophobic as well as polar character. Cellular membranes line CSF flow channels.…”
mentioning
confidence: 99%